Aktivitas Fisik Mahasiswa STKIP PGRI Sumenep Selama Bulan Ramadhan - Nugroho Agung Supriyanto; Abdul Azis (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2021)
The month of Ramadan is a month that requires Muslims to fasting from the sunrise until the sun sets. The month of Ramadan changes the pattern of physical activities. The aim of this study was to determine the level physical activity of STKIP PGRI Sumenep students during the month of Ramadan. This study uses a descriptive quantitative with the percentage method (%). The research subjects were 97 students. The results showed that 53 students (54.64%) were at the light level, 38 students (39.18%) were at the moderate level and 6 students were at the vigorous level (6.19%). Most students are at the light level because students also increase their level of worship during the month of Ramadan.